COMPARISON OF PLAQUE SCORE BETWEEN TRADITIONAL BRUSHING TEETH (MISWAK) AND BASS METHOD (Overview of Students of the Pondok Pesantren Darul Hijrah Putera Banjarbaru) - Rachmad Yamani; Rosihan Adhani; Diana Wibowo (FKG Unlam, 2020)
Background: Siwak or miswak is obtained from the branches and stems of the Salvadora persica plant that grows in the Middle Eastern plains and commonly used as a toothbrush to clean teeth and gingival structures. Miswak contains natural antibacterial acids (astringents, abrasives and detergents) which function to kill bacteria, prevent infection and stop bleeding in the gum. Chemical substances such as Chloride, Pottasium, Sodium Bicarbonate, Fluoride, Silica, Sulfur, Vitamin C, Trimethylamine, Salvadorine, and Tannins which function to clean teeth, whiten and nourish teeth and gingiva. How to brush your teeth has an effect on reducing or removing plaque. Efforts to clean plaque can be done by brushing your teeth. Brushing your teeth using a toothbrush is a form of mechanical removal of plaque. It can be done through several methods, including the method of Bass, Stillman, Fones, and adapted to the movements named Vertical and Horizontal. The bass method is a tooth brushing technique that is done by placing a 45-degree toothbrush on the root of the tooth and then gently pressing it while doing a small rotating motion. The tip of the toothbrush is directed to the gingival neck. The bass method is more effective for removing plaque around and below the edge of the gingiva. Controlled movements are used to get rid of plaque and avoid trauma to the gingiva. Objective: The purpose of this study was to analyze the comparison of plaque scores between brushing tooth with traditional (Miswak) and bass methods on students of the Pondok Pesantren Darul Hijrah Putera Banjarbaru. Method: This study used the Quasi experimental research method with Pre and Post-test. Results: The results of statistical tests using the non-parametric test of the Man Whitney test showed a value of p = 0,000 (p ≤ 0,05), the results showed that there were significant differences between the plaque scores before and after the tooth brushing treatment with the miswak and bass method. Conclusion: The bass method group has a lower plaque score than the miswak group.